FEatures of the prosecutorial supervision of legality of evidence of insanity in accordance with the requirements of the new Code of criminal procedure - Смирнова-Бартенєва, В. В. (Theory and practice of jurisprudence, 2016)
The article investigates to research of features of public Prosecutor’s supervision over the legality of evidence of insanity in accordance with the requirements of the new code of criminal procedure. Examines the role of the public Prosecutor in the process of proof in criminal proceedings for the application of compulsory measures of a medical nature.